Fine grained sport action recognition with Twin spatio-temporal convolutional neural networks application to table tennis - Martin, P. E.; Benois-Pineau, J.; Péteri, R.; Morlier, J. (Multimedia Tools and Applications, 2020)
Human action recognition in video is one of the key problems in visual data interpretation. Despite intensive research, the recognition of actions with low inter-class variability remains a challenge. This paper presents a new Twin Spatio-Temporal Convolutional Neural Network (TSTCNN) for this purpose. When applied to table tennis, it is possible to detect and recognize 20 table tennis strokes. The model has been trained on a specific dataset, so called TTStroke-21, recorded in natural conditions at the Faculty of Sports of the University of Bordeaux. Our model takes as inputs an RGB image sequence and its computed Optical Flow. The proposed Twin architecture is a two stream network both comprising 3 spatiotemporal convolutional layers, followed by a fully connected layer where data are fused. Our method reaches an accuracy of 91.4% against 43.1% for our baseline, a Two-Stream Inflated 3D ConvNet (I3D).